2019
DOI: 10.1002/ppul.24505
|View full text |Cite
|
Sign up to set email alerts
|

An in‐line high frequency flow interrupter applied to nasal CPAP: Improved carbon dioxide clearance in a premature infant lung model

Abstract: Background Noninvasive respiratory support continues to have high failure rates in small preterm infants. We previously demonstrated significantly improved in vitro CO2 washout by applying oscillations to a high flow nasal cannula system. Objective To develop a high frequency flow interrupter that could be applied to commonly used nasal continuous positive airway pressure (NCPAP) devices and to determine the effect of oscillations on end‐tidal carbon dioxide (EtCO2) levels in an infant lung model. Design/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This study was undertaken as a continuation of previous work performed in this laboratory in which a novel in-line flow interrupter device was evaluated to determine its efficacy as a simple means of improving carbon dioxide elimination in a nasal CPAP system 3,5 . We previously demonstrated that superimposing high frequency oscillation had better performance in improving carbon dioxide clearance when applied to a BCPAP system compared to the commonly used variable-flow type of nasal CPAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was undertaken as a continuation of previous work performed in this laboratory in which a novel in-line flow interrupter device was evaluated to determine its efficacy as a simple means of improving carbon dioxide elimination in a nasal CPAP system 3,5 . We previously demonstrated that superimposing high frequency oscillation had better performance in improving carbon dioxide clearance when applied to a BCPAP system compared to the commonly used variable-flow type of nasal CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, bubble nasal (BCPAP) has gained renewed interest not only due to its simplicity, but also because the random pressure oscillations caused by the bubbling have been suggested to improve gas exchange through mechanisms of action similar to those observed in high frequency ventilation 1,2 . In this regard, we have recently performed a series of in-vitro tests demonstrating improved carbon dioxide clearance when high frequency oscillations are superimposed onto the supply flow of a HFNC system 3,4 as well as onto the supply flow of a BCPAP system 5 . The aforementioned studies were exploratory proof-of-concept bench studies using a premature infant lung model having simulated normal, non-diseased, pulmonary mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…This study was undertaken as a continuation of previous work performed in this laboratory in which a novel in‐line flow interrupter device was evaluated to determine its efficacy as a simple means of improving CO 2 elimination in a nasal CPAP system 5 . We previously demonstrated that superimposing high‐frequency oscillation had better performance in improving CO 2 clearance when applied to a BCPAP system compared with the commonly used variable‐flow type of nasal CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In this regard, we have recently performed a series of in vitro tests demonstrating improved carbon dioxide (CO 2 ) clearance when high-frequency oscillations are superimposed onto the supply flow of an HFNC system 3,4 as well as onto the supply flow of a BCPAP system. 5 The aforementioned studies were exploratory proof-of-concept bench studies using a premature infant lung model having simulated normal, nondiseased, and pulmonary mechanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation